ChemInform Abstract: Development of a syn‐Selective Mannich Reaction of Aldehydes with Propargylic Imines by Dual Catalysis: Asymmetric Synthesis of Functionalized Propargylic Amines. Issue 41 (September 2016) - Lapuerta, Irati; Vera, Silvia; Oiarbide, Mikel; Palomo, Claudio
Abstract: Enolizable aldehydes are coupled with C‐alkynyl imines to produce an intermediate aldehyde adduct which is immediately reduced to the alcohol.